3D Heart Model and 4D Flow MRI 20 Years after Spiral Arterial Switch Operation - Sievers, Hans-Hinrich; Kheradvar, Arash; Kramer, Hans-Heiner; Rickers, Carsten (The Thoracic and Cardiovascular Surgeon Reports, 2016)
Case of a patient is presented here 20 years after spiral direct anastomosis of the great arteries in an arterial switch operation. Three-dimensional model of the heart combined with four-dimensional flow magnetic resonance imaging presents a novel comprehensive way to assess surgical results.
Keywords: transposition of great arteries; magnetic resonance imaging; physiological spiral anastomosis